Sistem Manajemen Lingkungan, Kinerja Lingkungan, dan Pengungkapan Emisi Karbon Perusahaan Energi di Indonesia - Dewi, Ni Putu Larasati Widyanti; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 34 No 3 (2024)DO - 10.24843/EJA.2024.v34.i03.p05, 2024)
This research aims to empirically prove the influence of environmental management systems and environmental performance on the disclosure of carbon emissions of energy companies in Indonesia with profitability and company size as control variables. The population in this study are energy companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The research sample was determined using a purposive sampling technique which resulted in 54 observations. The data analysis technique used is panel data regression. Based on the analysis results, it shows that the environmental management system and environmental performance have a significant effect on carbon emissions disclosure. Profitability and company size as control variables have no effect on carbon emissions disclosure. Keywords: Carbon Emission Disclosure; Company Size; Environmental Management System; Environmental Performance; Profitability